2012
DOI: 10.5761/atcs.cr.10.01654
|View full text |Cite
|
Sign up to set email alerts
|

Non-obstructive Mesenteric Ischemia: A Potentially Lethal Complication after Cardiovascular Surgery: Report of Two Cases

Abstract: We report two cases of non-obstructive mesenteric ischemia (NOMI), a rare but potentially lethal complication after cardiovascular surgery, which was successfully managed. In both cases (a 74-year-old chronic hemodialysis patient who underwent emergency aortic valve replacement and coronary artery bypass graft (CABG), and a 74-year-old patient who underwent emergency abdominal aortic aneurysm operation), NOMI occurred early postoperatively (on day 8 and 22, respectively). They suffered from severe abdominal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
1
11
0
5
Order By: Relevance
“…The most common pathophysiological explanation for intestinal ischemia in these patients is the systemic hypo perfusion state and splanchnic vasoconstriction that lead to NOMI [13,14]. In some studies, survivors of this complication have had surgical intervention earlier [5,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common pathophysiological explanation for intestinal ischemia in these patients is the systemic hypo perfusion state and splanchnic vasoconstriction that lead to NOMI [13,14]. In some studies, survivors of this complication have had surgical intervention earlier [5,11].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal ischemia after cardiac surgery most often is due to a non-occlusive mesenteric ischemia (NOMI) [13,14]. This condition was first described in 1958, and even though the exact pathophysiological mechanism is not understood, it is related to a reduction in the splanchnic blood flow, which can be due to low cardiac output, and it may also be aggravated by inotropic support such as vasopressors, and by pre-existing atherosclerosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal pain (reported to be absent in 23% of cases), bloody stools and progressive reduction of consciousness may then appear, leading, finally, to a picture of acute abdomen. 30,31 Angiography does not show vascular obstruction, but diffuse splanchnic vasospasm (Table 1). There are few published reports of CTA findings, which usually showed normal mesenteric vessels (both arteries and veins), associated with bowel wall thickening and pneumatosis (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In 1977, Boley demonstrated that the selective injection of papaverine into the SMA could relieve mesenteric vasoconstriction [3]. In addition, several reports have suggested the benefit of vasodilator therapy [2], [3], [5], [6], [7], [8] and one study concluded that selective mesenteric angiography with continuous vasodilator infusion was a simple, fast, and effective diagnostic and therapeutic tool to reduce the need for laparotomy [5]. Appropriate dosage levels for this therapy are not well established and in this case a lower dose than optimal was administered.…”
Section: Discussionmentioning
confidence: 99%